Early English Drama Records and Other Manuscripts from Coventry Destroyed Before and During the Second World War - Milne, Krista A. (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2023)
When Coventry’s central library was destroyed in 1940, valuable early guild records were lost. No consensus has emerged regarding which records were lost during the war and which records had been lost earlier. Identifying these losses is important, because Coventry’s records hold value for the city’s history and — since Coventry was a key site for early theatre — for Britain’s literary history. As this article shows, fewer historical manuscripts were destroyed in 1940 than was once feared. Moreover, the loss of one of these manuscripts is mitigated somewhat by new evidence presented here, which suggests that some of the manuscript’s source material survives.